Investigating The Effects of Twitter on Students’ English Writing Skill - Suharto, Ririn Pratiwi (EDUJ : English Education Journal, 2023)
With a limited number of characters per tweet, writing on Twitter requires creativity. It is unique media format has not only revolutionized online communication but also created a distinct style of writing. In this case, Twitter stands as a platform that reflects the way we write and communicate in English. Researcher wants to investigate the effects of twitter on students’ English writing skill. This is a case study method. This method helps the researcher to identify the problem in detail information. The data collected from questionnaire in English writing learning process. The lecturer becomes the observer or researcher of the research. On the other hand, students become the object of the research. As the conclusion, Twitter had a significant impact on students' writing skills in English. It challenges them to express their thoughts succinctly and effectively within a limited number of characters, encouraging creativity. However, it can also lead to errors and the use of informal language. Meanwhile, Twitter provides exposure to a variety of content and interactions with people from diverse backgrounds, which improves grammatical understanding. It also helps expand vocabulary by offering different words in context.